Bone marrow endothelial progenitors in atherosclerotic plaque resolution - Yao, Longbiao (Landes Bioscience, 2013)
Atherosclerosis is a major cause of morbidity and mortality in the United States. Persistently elevated circulating low-density lipoprotein, or hypercholesterolemia, and deposition of low-density lipoprotein in the vascular wall are the main inducers of atherosclerosis, which manifests itself as arterial lesions or plaques. Some plaques become thrombosis-prone and rupture, causing acute myocardial infarction or stroke. Lowering plasma cholesterol through the use of statins is the primary intervention against atherosclerosis. Treatment with statins slows progression of atherosclerosis but can only support limited plaque regression. Partially regressed plaques continue to pose a serious threat due to their remaining potential to rupture. Thus, new interventions inducing complete reversal of atherosclerosis are being sought. Implementation of new therapies will require clear understanding of the mechanisms driving plaque resolution. In this Commentary, we highlight the role of bone marrow endothelial progenitors in atherosclerotic plaque regression and discuss how regenerative cell-based interventions could be used in combination with plasma lipid-lowering to induce plaque reversal in order to prevent and/or reduce adverse cardiovascular events.